Roles of aromatic side chains and template effects of the hydrophobic cavity of a self-assembled peptide nanoarchitecture for anisotropic growth of gold nanocrystals. Issue 22 (15th November 2015) - Tomizaki, Kin-ya; Kishioka, Kohei; Kobayashi, Hiroki; Kobayashi, Akitsugu; Yamada, Naoki; Kataoka, Shunsuke; Imai, Takahito; Kasuno, Megumi
Graphical abstract: Abstract: Gold nanocrystals are promising as catalysts and for use in sensing/imaging systems, photonic/plasmonic devices, electronics, drug delivery systems, and for photothermal therapy due to their unique physical, chemical, and biocompatible properties. The use of various organic templates allows control of the size, shape, structure, surface modification and topology of gold nanocrystals; in particular, currently the synthesis of gold nanorods requires a cytotoxic surfactant to control morphology. To control the shape of gold nanocrystals, we previously demonstrated the de novo design and synthesis of a β-sheet-forming nonapeptide (RU006: Ac-AIAKAXKIA–NH2, X = l -2-naphthylalanine, Nal) and the fabrication of gold nanocrystals by mixing RU006 and HAuCl4 in water. The reaction afforded ultrathin gold nanoribbons 50–100 nm wide, several nanometers high, and microns long. To understand the mechanism underlying gold nanoribbon formation by the RU006 system, we here report (i) the effects of replacement of the Nal aromatic side chain in the RU006 sequence with other aromatic moieties, (ii) the electrochemical properties of aromatic side chains in the de novo designed template peptides to estimate the redox potential and number of electrons participating in the gold crystallization process, and (iii) the stoichiometry of the RU006 system for gold nanoribbon synthesis. Interestingly, RU006 bearing a naphthalene moiety (oxidation peak potential of 1.50 V vs Ag/Ag + ) and an analog [Ant 6 ]-RU006 bearing a bulky anthracene moiety (oxidation peak potential of 1.05 V vs Ag/Ag + ) allowed the growth of anisotropic (ribbon-like) and isotropic (round) gold nanocrystals, respectively. This trend in morphology of gold nanocrystals was attributed to spatially-arranged hydrophobic cavities sufficiently large to accommodate the gold precursor and to allow directed crystal growth driven by cross-linking reactions among the naphthalene rings. Support for this mechanism was obtained by decreasing the mole fraction of [Ant 6 ]-RU006 against the total concentration of [Ant 6 ]-RU006 and [Phe 6 ]-RU006: absorption spectra similar to that for RU006 were obtained. Differences in the redox properties of the anthracene and naphthalene moieties scarcely affected morphology. We propose that construction of an appropriate hydrophobic cavity is important for templating gold nanocrystal architectures by peptide self-assembly. This mechanism would be applicable for developing simple, low toxicity, mild synthetic methods for constructing metallic nanomaterials for therapeutic use.